Training in communication and emotion handling skills for students attending medical school: Relationship with empathy, emotional intelligence, and attachment style. Issue 9 (September 2022) - Donisi, Valeria; Perlini, Cinzia; Mazzi, Maria Angela; Rimondini, Michela; Garbin, Davide; Ardenghi, Stefano; Rampoldi, Giulia; Montelisciani, Laura; Antolini, Laura; Strepparava, Maria Grazia; Del Piccolo, Lidia
Abstract: Objective: To describe the Emoty-Com training, its impact on medical students' attitudes towards doctors' emotions and to explore the association between students' empathy, emotional intelligence (EI), and attachment style (AS) with post-training performance scores. Methods: The 16-hour Emoty-Com training was delivered to all second-year medical students of Verona and Milan (Italy) Universities. At pre-training, students filled out three questionnaires assessing empathy, AS and EI and responded to three questions on attitudes towards doctors' emotions in the doctor-patient encounter. The same three questions and a final evaluation test were proposed at post-training. Results: 264 students participated in the study. The training reduced students' worry about managing emotions during doctor-patient relationships. Gender was associated with specific subscales of empathy, EI, and AS. Final performance scores were associated with students' attitudes towards emotions but not with empathy, EI, and AS. Conclusion: The Emoty-Com training increased students' self-efficacy in handling their own emotions during consultations. Students' performance scores were related to their attitude towards doctors' emotions in clinical encounters. Practice Implications: The Emoty-Com training suggests ways to teach and evaluate emotion-handling skills for medical students. Possible links between empathy, EI, AS, and the attitudes towards doctors' emotions during the years of education are highlighted.